Improving the Storage Quality of Eggplants (Solanum Aethiopicum L.) Fruit using Aloe Vera Gel Coating - Dadzie, Rosemond Godbless; Amoah, Robert Sarpong; Ampofo-Asiama, Jerry; Quaye, Bright; Kizzie-Hayford, Nazir; Abano, Ernest Ekow (Journal of Food Technology Research, 2021)
Aloe vera gel has been investigated as possible edible coating to help improve the storage life of fruits after harvest. The study sought to investigate the effect Aloe vera gel coating with or without citric acid pretreatment on the quality of eggplant fruits during low temperature storage and in shelf life. Briefly, eggplants were coated with Aloe vera gel (some fruits were pretreated with citrate prior to the coating) and the changes in physicochemical quality of the fruit measured during storage at 10 °C. After 14 days, however, some fruits were transferred for storage at room temperature until day 18. Coating with Aloe vera decreased moisture loss, and consequently, decreased weight loss and loss of firmness of the fruit. The coating did help maintain the phenolic content, ascorbate levels and antioxidant capacity of the fruit. Pre-treating the fruit with citrate did not improve quality, showing that Aloe vera gel can be applied alone to enhance the storage quality of eggplant fruit. Results obtained from this study shows that Aloe vera gel coating can be useful in extending the postharvest storage life and maintaining the quality of eggplant fruits during low temperature storage.